International Relations Club Scrapbook (1932-1933) - (:unkn) unknown (My University, 1952)
In the years 1931-1932, the International Relations Club had four delegates go to the Annual Southern Conference of International Relations Club at Rollins College. the conference was a success and had an open discussion about how the faculty and advisors of the conference became interested in the Peace Movement. At the end of the pages in this section, there is a clip from the newspaper talking about an English Lecturer Mr. C. Douglas Booth a distinguished guest at the International Relations Club of Georgia State Woman's College.
International Relations Club (I.R.C). "1931-1932," 1952. 1 electronic record. 1 pdf document. 2 scans.
Keywords: International Relations Club; Scrapbook